Factors Affecting University Students’ Writing Proficiency in English in An Indonesian EFL Context - Hidayat, Agus; Kholid, M. Ridho (Raden Intan State Islamic University of Lampung, Indonesia, 2026)
This study aimed to investigate the factors affecting university students’ writing proficiency in English in an Indonesian EFL context. Employing a qualitative case study design, the research was conducted in 2025 at the English Education Program of Universitas Islam Negeri Raden Intan Lampung. Data were collected through semi-structured interviews with students and lecturers, classroom observations, and document analysis of students’ written works and instructional materials. The collected data were analyzed thematically to identify recurring patterns and relationships among influencing factors. The findings revealed that students’ writing proficiency was shaped by a complex interaction of motivational, strategic, linguistic, pedagogical, and environmental dimensions. Many students demonstrated low confidence and anxiety toward writing, which reduced their engagement in learning activities. In addition, limited use of effective learning strategies, such as planning and revising, hindered systematic writing development. Persistent grammatical and lexical weaknesses further constrained students’ ability to express ideas clearly and coherently. Teaching practices were generally supportive but limited by time constraints and large class sizes, resulting in insufficient individualized feedback. Moreover, restricted access to academic resources and limited extracurricular writing support reduced opportunities for extended practice. Overall, the study concludes that improving students’ writing proficiency requires an integrated approach that addresses affective, cognitive, linguistic, instructional, and institutional factors simultaneously